Analgesia epidural com clonidina ou sufentanil epidural em cadelas submetidas à ovariosalpingohisterectomia sob anestesia geral inalatória - Natalini, Claudio Correa (2011)
Background: Epidural administration of opioids and a2-adrenergic agonists allows the use of smaller doses when administered by other routes, providing analgesia during trans and post-anesthetic periods, reducing side effects and postoperative stress. Sufentanil in higher doses caused minimal hemodynamic changes in dogs. When given epidurally, clonidine produces analgesia without motor block by a non-opioid mechanism of action. The aim of this study was to evaluate the quality and duration of analgesia as well the cardiorespiratory changes resulting from administration of epidural clonidine or sufentanil in dogs anesthetized with halothane. Materials, Methods & Results: Twenty adult health dogs were used divided into two groups, clonidine (CLO) group and sufentanil (SUF) receiving 150 µg and 50 µg respectively epidural. After induction with thiopental and propofol in a mixture of equal parts (0.8 mg/kg), general anesthesia was maintained with halothane in a Bain circuit for further epidural administration of drugs. Heart rate and cardiac rhythm, respiratory rate, tidal volume, min volume, systolic arterial pressure, body temperature, oxygen saturation of oxyhemoglobin, halothane vaporization were evaluated at times T0 (baseline) and every 15 min until the end of the procedure (T1, T2, T3, T4). The arterial blood gas analysis was performed at T0G (baseline) and 30 min and 2 h after epidural (T1G, T2G) evaluating pH, PaO2 , PaCO2 , BE, HCO3 - and TCO2 . Postoperative analgesia was assessed by the scale of Firth & Haldane (1999) every hour for five hours, starting one hour after the surgery. All parametric variables were analyzed by use of a 1-way ANOVA for repeated measures, followed by a Dunnet test to compare all sample collection times with baseline data (0 min). For comparisons among groups, for each time, test t was used. Differences were considered significant when P < 0.05. The results showed a significant reduction in heart rate after 15 min lasting for 60 min with a reduction in SAP, but no signs of hypotension. A reduction in respiratory rate was also observed in the SUF group and vaporization of halothane in both groups with increase in SpO2 . There was no difference in cardiac rhythm and tidal volume, there was only an increase in minute volume at 60 min in the SUF group. Body temperature also decreases at all times. Discussion: The reduction in heart rate was observed since sufentanil have discrete sympatholytic and vagotonic activity and a2-adrenergic agonists may also cause bradycardia by vagomimetic effect. The drugs used can also cause a reduction in blood pressure, but hypotension was not observed in this study, corroborating with several authors. The lipophilic opioids suffer greater absorption by the blood vessels in the epidural region resulting in peak plasma concentration and early respiratory depression, while the a2-adrenergic agonists cause respiratory depression secondary to central nervous system depression. The observed reduction in vaporization is due to potentiation of drugs used. Analgesia in the intraoperative period can be proved since tachycardia, tachypnea, or hypertension during clamping of the ovarian pedicles was not observed and in the immediate postoperative period, both drugs proved effective with Firth & Haldane numerical scale. The doses employed by epidural reduced the need for halothane demonstrating intra-operative analgesic effect. Furthermore, sufentanil caused severe respiratory depression, however it is suggested greater efficacy when compared to clonidine in the immediate postoperative period.